Answer: -0.833 (repeating decimal)
Step-by-step explanation: fg(x) means plug the g(x) equation into f(x), and for gf(x) it’s vice versa:
Fg(x) = 3x^2 - 1 + 2
Gf(x) = 3(x + 2)^2 - 1
First, we should simplify gf(x) to eliminate the (x + 2)^2:
3(x^2 + 4x + 4) - 1
3x^2 + 12x + 12 - 1
3x^2 + 12x + 11
Second, simplify fg(x) by solving -1 + 2: 1
Now, we can set the two equations equal to each other and solve:
3x^2 + 1 = 3x^2 + 12x + 11 (subtract 3x^2 from each other and 1 from 11)
-10 = 12x (Divide)
-0.8333... = x
To make sure this answer is correct, plug -0.833 into the original equations and set them equal to each other:
3(-0.833)^2 + 1 = 3(-0.833)^2 + 12(-0.833] + 11
3.083 = 3.083